Interactions between common bottlenose dolphins (Tursiops truncatus) and the artisanal fishery in Asinara Island National Park (Sardinia): assessment of catch damage and economic loss - Lauriano , G.; Fortuna , C. M.; Moltedo , G.; Notarbartolo Di Sciara, G. (J. Cetacean Res. Manage., 2023)
In 1999, the Italian Central Institute for Applied Marine Research (ICRAM), in response to reports made by local fisheries, began a study into the interactions between common bottlenose dolphins (Tursiops truncatus) and the artisanal fishery in the Asinara Island National Park (Sardinia). Using onboard observers, fishing boat surveys were carried out to determine the frequency of interactions, variations in the catch of target species and damage to two different types of trammel net caused by dolphins. Interactions occurred primarily with trammel nets targetting striped red mullet (Mullus surmuletus; the less valuable peacock wrasse, Simphodus tinca, was also caught). Interactions also occurred with trammel nets set for lobster (Palinurus elephas), cuttlefish (Sepia spp.) and scorpionfish (Scorpaena spp.), but these were considered negligible. The target species, catch and damage inflicted on the catch was recorded, both in the presence and absence of dolphins, in an effort to ascertain associated damage and economic cost. Loss of catch was found to be significant only in the case of nets deployed during the red striped mullet fishing season. Although the level of interaction was high relative to the narrow red striped mullet fishery season, the overall economic impact on the fishing community was found to be modest. The presence and regulations of the national park area may provide an opportunity for investigating mitigation activities compatible with both cetacean conservation and the maintenance of the traditional fisheries.